BALANCING BUDGET AND RAISING EFFECTIVENESS OF PUBLIC DEBT SERVICE MARKET FOREXAMPLE OF POLAND IN 2007/2008 (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of this paper is to describe two vital aspects of present-day budgetary pol-icy, namely: balancing the fiscal bill and developing (strengthening) the debt service market. In the first part of this paper I trying to explain the role which is played by effi-cient public debtmarket in process of balancing public finance, especially in recession time. The second part of this document was dedicated to examine thesis that unplanned government expenditures are harmful for situation of public debt market. Increase of finance government activity leads to rise the value of treasury bonds in the structure of instruments using to borrow money in order to cover public finance deficit. It down-grades the condition of public debt market and it has negative impact on effectivenessof this market. In slump time government is forced to use all accessible budgetary instru-ments to balance public account. What is more, it causes that state of debt market be-comes less important than balancing the public finance bill. For this reason, recession deteriorates situation of debt service market.
Keywords: budgetary policy, fiscal bill, public debt market, debt service market, reces-sion, treasury bond, securities